Standardizing the measurement of maternal morbidity: Pilot study results - Barreix, Maria (Int J Gynaecol Obstet, 2018)
OBJECTIVE: To field test a standardized instrument to measure nonsevere morbidity among antenatal and postpartum women. METHODS: A cross‐sectional study was conducted in Jamaica, Kenya, and Malawi (2015–2016). Women presenting for antenatal care (ANC) or postpartum care (PPC) were recruited if they were at least 28 weeks into pregnancy or 6 weeks after delivery. They were interviewed and examined by a doctor, midwife, or nurse. Data were collected and securely stored electronically on a WHO server. Diagnosed conditions were coded and summarized using ICD‐MM. RESULTS: A total of 1490 women (750 ANC; 740 PPC) averaging 26 years of age participated. Most women (61.6% ANC, 79.1% PPC) were healthy (no diagnosed medical or obstetric conditions). Among ANC women with clinical diagnoses, 18.3% had direct (obstetric) conditions and 18.0% indirect (medical) problems. Prevalences among PPC women were lower (12.7% and 8.6%, respectively). When screening for factors in the expanded morbidity definition, 12.8% (ANC) and 11.0% (PPC) self‐reported exposure to violence. CONCLUSION: Nonsevere conditions are distinct from the leading causes of maternal death and may vary across pregnancy and the puerperium. This effort to identify and measure nonsevere morbidity promotes a comprehensive understanding of morbidity, incorporating maternal self‐reporting of exposure to violence, and mental health. Further validation is needed.